Performance Evaluation for Polymer-Stabilized Soils. Issue 1 (January 2017) - Rezaeimalek, Sepehr; Huang, Jie; Bin-Shafique, Sazzad
A poorly graded natural sand was stabilized by using a liquid polymer soil stabilizer from the generic family of styrene acrylics. The stabilized specimens were tested for short-term performance and durability. Short-term performance was evaluated by testing the specimens for unconfined compressive strength shortly after specimen casting. Durability was assessed by testing the specimens that were aged under different scenarios, that is, 24 wet–dry cycles, 24 freeze–thaw cycles, and 8 months of outdoor exposure. In addition, the fatigue response of the stabilized specimens was evaluated by testing their fatigue resistance after 1, 000, 000 cycles of repetitive loading with 500 and 700 microstrains. The results of such evaluations suggest an acceptable performance of the aged specimens, with limited strength loss after aging. In the fatigue test, the specimens showed a perfectly elastic behavior with no sign of failure. However, because of the unique nature of the test results, further inspections should be conducted to have a better understanding of the potential for using liquid polymer soil stabilizers in pavements.